Fractures of the proximal- and middle-thirds of the humeral shaft should be considered as fragility fractures: an epidemiological study of 900 consecutive injuries. (7th November 2020) - Oliver, William M.; Searle, Henry K. C.; Ng, Zhan Herr; Wickramasinghe, Neil R. L.; Molyneux, Samuel G.; White, Tim O.; Clement, Nicholas D.; Duckworth, Andrew D.
Abstract : Aims: The aim of this study was to determine the current incidence and epidemiology of humeral diaphyseal fractures. The secondary aim was to explore variation in patient and injury characteristics by fracture location within the humeral diaphysis. Methods: Over ten years (2008 to 2017), all adult patients (aged ≥ 16 years) sustaining an acute fracture of the humeral diaphysis managed at the study centre were retrospectively identified from a trauma database. Patient age, sex, medical/social background, injury mechanism, fracture classification, and associated injuries were recorded and analyzed. Results: A total of 900 fractures (typical 88.9%, n = 800/900; pathological 8.3%, n = 75/900; periprosthetic 2.8%, n = 25/900) were identified in 898 patients (mean age 57 years (16 to 97), 55.5% (n = 498/898) female). Overall fracture incidence was 12.6/100, 000/year. For patients with a typical fracture (n = 798, mean age 56 years (16 to 96), 55.1% (n = 440/798) female), there was a bimodal distribution in men and unimodal distribution in older women (Type G). A fall from standing was the most common injury mechanism (72.6%, n = 581/800). The majority of fractures involved the middle-third of the diaphysis (47.6%, n = 381/800) followed by the proximal- (30.5%, n = 244/800) and distal-thirds (n = 175/800, 21.9%). In all, 18 injuries (2.3%) were open and a radial nerve palsy occurred in 6.7% (n = 53/795). Fractures involving the proximal- and middle-thirds were more likely to occur in older (p < 0.001), female patients (p < 0.001) with comorbidities (p < 0.001) after a fall from standing (p < 0.001). Proximal-third fractures were also more likely to occur in patients with alcohol excess (p = 0.003) and to be classified as AO-Orthopaedic Trauma Association type B or C injuries (p < 0.001). Conclusion: This study updates the incidence and epidemiology of humeral diaphyseal fractures. Important differences in patient and injury characteristics were observed based upon fracture location. Injuries involving the proximal- and middle-thirds of the humeral diaphysis should be considered as fragility fractures. Cite this article: Bone Joint J 2020;102-B(11):1475–1483.